Comparing sleep in shared and individual rooms during training camps in elite youth soccer players: a short report - Costa, J. A.; Figueiredo, P.; Lastella, M.; Nakamura, F. Y.; Guilherme, J.; Brito, J. (Journal of Athletic Training, 2023)
Context Athletes' sleep is the most important recovery strategy and has received growing attention. However, athletes may experience sleep disruptions due to numerous factors, such as training and competition workloads, travel, changes in sleep-wake schedules, and sleeping environments. They often spend nights in unfamiliar hotels, and sharing a bed, room, or both with another person might affect sleep duration and quality.